Quality of Life and Healh of Senior High School in Lublin - Marlena Maria Duda (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The increasing number of children and young people struggling with chronic diseases and other health problems indicates the need for a closer look at the problem of difficulties in the functioning of psychosocial resulting from ill health. Diagnosing the level of sense of life quality depends on the health of high school students is a necessary procedure in order to identify opportunities for early intervention in countering the negative psychosocial effects of chronic disease. Determining the level of sense of life quality for high school students with health problems compared to healthy peers was conducted. There were examined 251 students in Lublin high schools. Standardized diagnostic questionnaire KIDSCREEN-52 by J. Mazur et al. was used. Results obtained during the analysis of evidence suggest that health-related quality of life of young people with health problems is significantly lower than in healthy peers, both in the case of complete physical, mental and psychosocial functioning in the school environment. Particularly noteworthy are the dimensions of felt emotions, psychological well-being, self-image, and the school environment.